Autoethnographic Analysis of Local Television Presenters in Maintaining Regional Language News amid the Pressure of Global Cultural Homogenization - Huki, Riska Lapiani; Solihin, Olih; Soegoto, Eddy Soeryanto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The challenge of homogenizing global culture is currently a challenge for public broadcasting institutions, especially for local television media in maintaining regional language news broadcasts. This study aims to explore the strategic role of local television news presenters in maintaining the regional language (Sundanese) as a cultural identity in the midst of global cultural homogenization. This study uses a qualitative approach with the Analytical Autoethnography method. The researcher, who also serves as a presenter at the institution, reflects deeply on his professional experience. The data was strengthened through interviews with news management as key informants, as well as audience response analysis through synthetic narrative techniques to validate the regional language news program on the impact on the social environment. The results showed that presenters negotiated identity through the use of customary attributes and authoritative language and improvisation that did not change the meaning. Special segments such as Peupeureunian and Rincik Rincang act as living cultural archives that maintain the collective memory of the community. This study concludes that local public media serves as an effective cultural haven in countering global homogeneity. The implications of this study suggest the importance of modern visual adaptations of traditional content to appeal to the younger generation without sacrificing the noble values of the mother tongue.